2021
DOI: 10.1007/s12262-021-02945-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Complete Response After Neoadjuvant Therapy in Rectal Adenocarcinoma: a 5-Year Follow-up

Abstract: Neoadjuvant therapy is the gold standard treatment of locally advanced rectal cancer. It may induce complete sterilization of tumor cell and decreases its local recurrence rate. While 15-20% of patients were found to have pathological complete response (pCR) with combined multimodal therapy, Asian data were generally scarce. pCR rate can indicate the suitability of applying the "watch-and-wait" strategy, which advocates deferment of surgery that can alleviate surgery-associated morbidity.To determine the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Early reports with 2-year and 5-year follow-up periods showed improved overall survival, decrease in the local and distant recurrence rates, and high tumor-specific survival rates in patients with cPR [20,42,43]. Recent reports with follow-up periods up to 10 years are also in favor of the absence of local recurrence and an excellent disease-free survival rate of 95% [24,34,44]. This study also reports a high survival rate for patients with TRG0 and TRG1.…”
Section: Discussionsupporting
confidence: 60%
“…Early reports with 2-year and 5-year follow-up periods showed improved overall survival, decrease in the local and distant recurrence rates, and high tumor-specific survival rates in patients with cPR [20,42,43]. Recent reports with follow-up periods up to 10 years are also in favor of the absence of local recurrence and an excellent disease-free survival rate of 95% [24,34,44]. This study also reports a high survival rate for patients with TRG0 and TRG1.…”
Section: Discussionsupporting
confidence: 60%
“…Studies have revealed [ 13 ] that younger patients are more likely to obtain a good pathological response, consistent with our findings, because younger patients may have a stronger immune response to NCRT. However, several studies [ 14 , 15 ] revealed no significant statistical significance between age and pathological response after NCRT, and even Leow’s [ 16 ] study indicated that young age was a predictor of a lower pCR rate after NCRT because young patients may have more aggressive pathological features, associated with higher CD133 + cancer stem cell burden, thereby resulting in a poorer response to neoadjuvant therapy. Further investigation is needed on the pathological response of age to NCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al in 2020 found young patients (<40 years old) had lower pCR rates [35]. A 2021 study out of Malaysia further supported those findings, with lower pCR rates after neoadjuvant CRT [48]. However, a 2013 study from Memorial Sloan-Kettering, found similar pCR rates despite early-onset rectal cancer [49].…”
Section: Patient Demographicsmentioning
confidence: 94%
“…Other studies have shown age is not associated either positively or negatively with pCR [50]. A hypothesis for future research to explore is if younger patients have other tumor and patient characteristics, including more aggressive features, that are not responsive to treatment [48] or if younger patients are more likely to receive maximum and aggressive treatment [36] with no actual differences in pCR rate based on age.…”
Section: Patient Demographicsmentioning
confidence: 97%